Demicompact linear operators, essential spectrum and some perturbation results. Issue 13 (15th May 2015) - Chaker, Wajdi; Jeribi, Aref; Krichen, Bilel
<x xml:space="preserve">Abstract</x> In this paper, we present some results on Fredholm and upper semi‐Fredholm operators involving demicompact operators. Our results generalize many known ones in the literature, in particular those obtained by Petryshyn in 26 and Jeribi et al. in 1, 21. They are used to establish a fine description of the Schechter essential spectrum of closed densely defined operators, and to investigate the essential spectrum of the sum of two bounded linear operators defined on a Banach space by means of the essential spectrum of each of the two operators.